Genome-Wide Association Study of Susceptibility Loci for TCF3-PBX1 Acute Lymphoblastic Leukemia in Children. (14th September 2020) - Lee, Shawn H. R; Qian, Maoxiang; Yang, Wentao; Diedrich, Jonathan D; Raetz, Elizabeth; Yang, Wenjian; Dong, Qian; Devidas, Meenakshi; Pei, Deqing; Yeoh, Allen; Cheng, Cheng; Pui, Ching-Hon; et al.
Abstract: Acute lymphoblastic leukemia (ALL) is the most common cancer in children. TCF3-PBX1 fusion defines a common molecular subtype of ALL with unique clinical features, but the molecular basis of its inherited susceptibility is unknown. In a genome-wide association study of 1494 ALL cases and 2057 non-ALL controls, we identified a germline risk locus located in an intergenic region between BCL11A and PAPOLG : rs2665658, P  =   1.88 × 10 –8 for TCF3-PBX1 ALL vs non-ALL, and P  =   1.70 × 10 –8 for TCF3-PBX1 ALL vs other-ALL. The lead variant was validated in a replication cohort, and conditional analyses pointed to a single causal variant with subtype-specific effect. The risk variant is located in a regulatory DNA element uniquely activated in ALL cells with the TCF3-PBX1 fusion and may distally modulate the transcription of the adjacent gene REL . Our results expand the understanding of subtype-specific ALL susceptibility and highlight plausible interplay between germline variants and somatic genomic abnormalities in ALL pathogenesis.